The structure of production in Romanian agriculture - the gap between the EU27 - Voicu, Radu; Turek Rahoveanu, Adrian; Ion Raluca, Andreea (Economics of Agriculture, 2010)
The paper aims to capture the differences between the production structures of different countries and differences existing in some respects, between Romania and EU. In achieving this, the comparison and analysis methods of statistical data are used. Results show that gaps between agriculture of EU27 countries are found in terms of expansion known by different industries and cultures, rather than the kind of branches practiced. Different production structures and, particularly, development of agriculture of various countries generate differences on synthetic results obtained by them and their contribution to economic growth. Such a thing must be a strong reason for reflection and, in particular, for action for all those directly connected to the situation of Romanian agriculture.